Tecnologias leves na experiência do programa rede de oficinandos na saúde da Ufersa, em Mossoró – RN - Lima, Lia Rodrigues Lessa de (Universidade Federal Rural do Semi-Árido, 2018)
This search aims to understand how the institution of the CAPSi in the city of Mossoró, located in the state of Rio Grande do Norte, welcomes and supports the making of the Programa Rede de Oficinandos na Saúde, a university extension action that has been implemented in this center since february 2012. This action constitutes a paradigmatic link of the network that emerged from the Psychiatric Reform and the Antimanicomial Struggle. We seek to understand the historical course of this action, the conception of its methodology as an alternative of care and attention in mental health, the transformations and disruptions that the action promotes in the environment and in the scenario constituted of professionals, family, children and teenagers , as well as the modes of coupling of this action by the institution management. The theoretical framework that supports the analysis counts especially on the studies of Amarante, Foucault, Maturana, Varela, Balman and Maraschin, among others. The method that we will use in the analysis is the intervention research and the methodology that we will adopt is entitled first person methodology with emphasis on listening to the self-authoring of the participants and forms of authorship, such as narratives present in the researcher's personal journals and videos, which were authorized and hosted in this Psychosocial Care Center as a way of access information. As results we explain how a methodology that is conducted according to Federal Mental Health Policies is welcomed in the institution and, thus, provide subsidies for our reflection on the use of light technologies as an alternative methodology of care in mental health
Keywords: Reforma psiquiátrica; Ambiente sensível; Pesquisa intervenção; Tecnologias leves; Psychiatric reform; Sensitive environment; Intervention research; Light technologies; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE